Fundamentals of athletic training - Cartwright, Lorin 1956- MS, ATC, CAA; Peer, Kimberly S. EdD (Champaign, IL Human Kinetics, 2019)
Fundamentals of athletic training, fourth edition, offers a well-rounded introduction to the field of athletic training. It presents injuries and illnesses commonly encountered by certified athletic trainers and also reviews professional and administrative aspects of the profession. Written specifically for high school and community college students, this text provides foundational knowledge and skills as well as the opportunity for students to evaluate the possibility of a career as a sports medicine professional. The fourth edition presents the latest developments in athletic training with regard to treatment, care, administration, and certification. New material in this edition includes the following: professional preparation and career potential; documentation, record keeping, and electronic injury tracking systems; development and design of an athletic training facility; fiscal management and equipment ordering; analysis of preexisting conditions and preparticipation exams; basic diagnostic tests, including x-rays, ultrasounds, and drug screening tests; ethics for sports medicine professionals. The fourth edition also features a web resource that includes 28 practical skills worksheets and a semester-long project that develops with each chapter to give students a true understanding of the requirements needed to be an effective athletic trainer.
1. Athletic training as a profession -- 2. Administration and professional development -- 3. Design and development of the athletic training facility -- 4. Documentation and record keeping -- 5. Fiscal management -- 6. The preparticipation physical exam -- 7. Introduction to anatomy -- 8. Basics of tissue injuries -- 9. Head injuries -- 10. Facial injuries -- 11. Throat and thorax injuries -- 12. Abdominal injuries -- 13. Spinal injuries -- 14. Shoulder injuries -- 15. Elbow injuries -- 16. Wrist and hand injuries -- 17. Hip, pelvis and thigh in juries -- 18. Knee injuries -- 19. Foot, ankle, and lower-leg injuries -- 20. Patient assessment and treatment methods -- 21. Reconditioning programs -- 22. Psychological aspects of athletic training -- 23. Planning for emergencies -- 24. Primary and secondary procedures -- 25. Environmental situations and injuries -- 26. Stabilization and transportation of injured athletes -- 27. Protective taping and wrapping -- 28. Protective equipment used in athletics -- 29. Basic diagnostic imaging and testing -- 30. Conditions and illnesses -- 31. Communicable disease -- 32. Common drugs used in athletics -- 33. Nutrition and weight control -- 34. Athletes with disabilities or disorders
Includes bibliographical references and index
Keywords: Athletic trainers